Efficacy and safety of massage therapy for autism spectrum disorders: A protocol for systematic review and meta-analysis. Issue 19 (14th May 2021) - Guo, Sheng; Zhou, Ke-Lin; Dong, Shuo; Xue, Xiao-Na; Wei, Pei-Dong; Yang, Jing-Yi; Fu, Guo-Bing; Liu, Zhen-Bo; Cui, Xia
Abstract: Background: Autism spectrum disorder is a neurodevelopmental disorder with increasing incidence. At present, the global incidence of the disease is on the rise, and the cause is unknown. There is no specific treatment for this disease at present, mainly education and training. Traditional Chinese medicine treatment has a certain effect on the improvement of the symptoms of the disease. The treatment methods are mainly oral Chinese medicine and acupuncture, but children are often not easy to cooperate. As a safe and effective green therapy, massage is easy to be accepted by children. Methods: We will search the following electronic databases for randomized controlled trials to evaluate the effectiveness and safety of massage therapy in treating autism spectrum disorders: Wanfang and PubMed Database, China National Knowledge Infrastructure Database, Cochrane Central Register of Controlled Trials, Cumulative Index of Nursing and Allied Health Literature, and Excerpta Medica database. Each database will be searched from inception to March 2021. The entire process will include study selection, data extraction, risk of bias assessment, and meta-analyses. Results: This proposed study will evaluate the effectiveness and safety of massage therapy for patients with autism spectrum disorders. The outcomes will include changes in autism spectrum disorder relief and adverse effect. Conclusion: This proposed systematic review will evaluate the existing evidence on the effectiveness and safety of massage therapy for patients with autism spectrum disorders. Dissemination and ethics: The results of this review will be disseminated through peer-reviewed publication. Because all of the data used in this systematic review and meta-analysis have been published, this review does not require ethical approval. Furthermore, all data will be analyzed anonymously during the review process.